2021
DOI: 10.17582/journal.jahp/2021/9.3.296.302
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Disinfection on Airborne and Waterborne Fungal Load in Broiler Chicken Houses

Abstract: Several studies have looked at the bacterial population in poultry houses, but there have been few papers on mycological contamination; especially isolation of fungal isolates from cooling pads' water. As a consequence, this research aimed to isolate and identify airborne and waterborne fungi from a variety of surfaces in two closed broiler chicken housing in the Giza government. This study was carried out during the flocks' growth period (on day 10, day 30, and two hours after disinfection). Twenty water samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Our study's results showed a significant difference between ages 7, 21, and 31 days in the TCC due to the hygienic condition of the poultry house during the growing period (P < 0.05). As organic matter and dandruff increased with aging, it was not surprising that the TFC varied at different sampling times; this is consistent with [39]. Like this, the TCC and TCFC showed that the number of microorganisms in floor dust (Table 3) was significantly different (P <0.05) at the age of 31 days than at the age of 7 days due to the increase in dust on the floor.…”
Section: Discussionsupporting
confidence: 80%
“…Our study's results showed a significant difference between ages 7, 21, and 31 days in the TCC due to the hygienic condition of the poultry house during the growing period (P < 0.05). As organic matter and dandruff increased with aging, it was not surprising that the TFC varied at different sampling times; this is consistent with [39]. Like this, the TCC and TCFC showed that the number of microorganisms in floor dust (Table 3) was significantly different (P <0.05) at the age of 31 days than at the age of 7 days due to the increase in dust on the floor.…”
Section: Discussionsupporting
confidence: 80%
“…and/or Fusarium spp. Can be observed in water lines, cooling pad water, fans, and floors of broiler farms [ 19 ]. These factors compromise the quality of water and air in poultry facilities.…”
Section: Poultry Farms Are An Ideal Environment For Undesirable Micro...mentioning
confidence: 99%